Early adverse life events and post‐traumatic stress disorder in patients with constipation and suspected disordered defecation. Issue 3 (14th June 2021) - Hendrix, Justin; Ranginani, Dheeksha; Montero, Anne Mary; Lockett, Carolyn; Xu, Huiping; James‐Stevenson, Toyia; Shin, Andrea
Abstract: Background: Early adverse life events (EALs) and post‐traumatic stress disorder (PTSD) are associated with irritable bowel syndrome (IBS). Disordered defecation (DD) presents with symptoms of IBS or functional constipation (FC) and is associated with psychological distress. However, the role of trauma and stress in chronic constipation is poorly defined. We aimed to examine EALS, PTSD, and psychological symptoms in patients with constipation and suspected DD. Methods: We conducted a survey study among adults with constipation who completed anorectal manometry (ARM) and balloon expulsion testing (BET). Data were collected on socio‐demographics, EALs, PTSD, bowel symptoms, quality of life, and anxiety and depression. We performed comparisons between individuals with normal versus abnormal ARM or BET, subgroup analysis by detailed ARM and BET findings, and latent class analysis using individual EAL domains. Key Results: Among 712 eligible patients, 69 completed the study. EALs and provisional PTSD were present in 75.4% and 27.5%, respectively; rates did not differ between those with normal versus abnormal ARM or BET. Normal testing was associated with higher rates of specific EAL domains (emotional abuse and mental illness), higher depression scores, and poorer mental component scores in both primary and subgroup comparisons (all p  < 0.05). Normal testing was associated with a lower likelihood of high‐EAL latent class ( p  = 0.01) membership. Presence of IBS or FC did not influence associations. Conclusions & Inferences: Early adverse life events and PTSD are prevalent in patients with constipation and suspected DD. Those with normal ARM and BET have higher rates of prior emotional abuse and poorer mental health. Abstract : Prevalence rates of early adverse life events (EALs) and post‐traumatic stress disorder PTSD are high among patients with severe constipation and suspected defecation disorders. Patients with normal anorectal manometry and balloon expulsion test appear to be at higher risk of prior emotional abuse and poorer mental health than patients with abnormal testing.